Challenged but not threatened: Managing health in advanced age. (April 2019) - Wiles, Janine; Miskelly, Philippa; Stewart, Oneroa; Kerse, Ngaire; Rolleston, Anna; Gott, Merryn
Abstract: In this paper we reflect on discussions with people of advanced age in Āotearoa New Zealand, and draw on theoretical frameworks of resilience and place in old age, to explore insights about the ways older people maintain quality of life and health. Twenty community-dwelling people of advanced age (85+) were recruited in 2015–16 from a large multidisciplinary longitudinal study of advanced age. These twenty participated in interviews about health in advanced age, impact of illnesses, interactions with clinicians, access to information, support for managing health, and perceptions of primary care, medications, and other forms of assistance. We use a positioning theory framework drawing on thematic and narrative analysis to understand the dynamic ways people in advanced age position themselves and the ways they age well through speech acts and storylines. People in advanced age saw themselves as challenged, rather than threatened, by adversities, and positioned themselves as able to draw on a lifetime of experience and resourcefulness and collaborations with supporters to deal with challenges. Key strategies include downplaying illness and resisting biomedical discourses of complexity, positioning embodied selves as having agency, and creative adaptation in the face of loss. People in advanced age exhibit resilience, maintaining wellbeing, autonomy and good physical and mental quality of life even while living with challenges such as functional decline and multi-morbidities. These findings have significance for supporters of older people, emphasising the need to move away from a narrow focus on problems to working together WITH people in advanced age to offer a more holistic approach that encourages and enhances adaptation and flexibility, rather than rigid and counterproductive coping patterns. Highlights: Older people position themselves as active co-managers in their support arrangements. Framing problems as challenges not threats facilitates older people's resourcefulness. People in old age adapt resiliently to health conditions as part of living and ageing.